MICROORGANISMS IN REGIONS OF ACTIVE VOLCANISM AND THE FORMATION OF NEW GOLD - Korobushkina Ye.D.; Koroleva G.P. (My University, 1989)
We are the first to have obtained information concerning the effect of thermophilic organisms on the behavior of gold. The air of our work was to find microbic and algal-bacterial coenoses and ascertain their role in accumulating and coarsening gold in the supergene alteration zone of geothermal areas. For microbiologic and geochemical investigation, we sampled thermal water and altered rocks of the Lower Kosheleva geyser field, as well as thermal water of the Sivuchiy Springs and bottom deposits of the Sea of Okhotsk. The work was done on microorganism communities extracted from water, altered rock and bottom sediment. The microorganisms were cultivated in standard media as well as in media with dissolved and colloidal gold. The results show that the development of microorganism communities depends on the physicochemical conditions. Our experiments revealed the specific mode of interaction of dissolved and colloidal gold with natural biocoenoses that had been extracted from natural samples collected in southern Kamchatka and from bottom deposits in the Sea of Okhotsk. The above data indicate that algal-bacterial communities in regions of active volcanism may help to form zones where gold will accumulate and become coarser.